Uterine Septum Dimensions in Patients with Infertility and Recurrent Abortion and the Outcomes of Hystroscopic Metroplasty - S Masihi; M Barati; F Marmazi; M Tork zaban (Journal of Kerman University of Medical Sciences, 2010)
Background & Aims: It is believed that uterine septum, because of its effect on infertility and recurrent abortion is very important and pregnancy outcome is obviously improved by hysteroscopic metroplasty (HM). In this study, the probable relationship of uterine septum dimensions (length and width) with infertility and recurrent abortion has been investigated. Methods: This clinical trial was carried out from Jan. 2004 to Feb. 2007 on all patients referred to Ahwaz educational hospitals for evaluation of infertility and recurrent abortion and underwent hysterosalpingography (HSG). Patients with suspected uterine septum were referred to Imam Khomeyni Hospital and underwent simultaneous hysteroscopy and laparoscopy. After that hysteroscopic metroplasy was done. The participants were checked by new HSG after one month and were evaluated for pregnancy outcome after one year. Results: In whole, 50 patients (28 cases with infertility and 22 cases with recurrent abortion) were studied. In 62.5% septum width was equal or less than 3cm and in 48% length of septum occupied two thirds of uterine cavity and there was no significant difference between the tow groups in regard to septum's width and length. Rate of pregnancy occurrence was 71.4% in patients with infertility and 76.5% in patients with recurrent abortion and no significant difference was found between the two groups in this regard. Conclusion: According to the findings, it seems that septum dimensions (width and length) have no role in infertility and abortion. Therefore, resection of uterine septum regardless of its size is recommended. In patients with uterine septum who suffer from infertility and recurrent abortion, HM is an appropriate approach.